Aplikasi Google Meet dan Power Point untuk Pembelajaran Sejarah Indonesia pada Masa Pandemi Covid-19 - Stepanus Harinto (Proceedings Series on Social Sciences & Humanities, 2021)
The learning approach of Indonesia History using by Google Meet and Power Point in Covid 19 Pandemi era have background of the application by WhatsApp, Google Classroom, MsWord, Google Form, Google Drive hasn’t been resulted in daily assessment is very bad. This application increase the meeting by using Google Meet and Power Point. The purpose of it to develop the result of the daily assessment for students in studying Indonesia History in class AKL 1 SMK Negeri 1 Bawang in the second semester of 2020-2021. By addition of this application of Google Meet and Power Point in rate of 75, after the application has been done the result is about 80, 28. It can be included that the increasing of the application of Google Meet and Power Point is very useful significantly.